pH-Responsive Nanoparticles for Delivery of Paclitaxel to the Injury Site for Inhibiting Vascular Restenosis - Huiru Zhu; Li Kong; Xu Zhu; Tingting Ran; Xiaojuan Ji (MDPI AG, 2022)
A high incidence of restenosis has been reported at the site of inflammation following angioplasty and stent implantation. The anti-proliferative drug paclitaxel (PTX) could help to reduce inflammation and restenosis; however, it has poor water solubility and serious adverse side effects at high doses. Given the presence of metabolic acidosis at the site of inflammation, we hypothesized that nanoparticles that are responsive to low pH could precisely release the loaded drug at the target site. We successfully constructed pH-responsive poly(D, L-lactic-co-glycolic acid) (PLGA) nanoparticles loaded with PTX and NaHCO3 as a pH-sensitive therapeutic agent (PTX-NaHCO3-PLGA NPs). The NPs exhibited remarkable pH sensitivity and a good safety profile both in vitro in rat vascular smooth muscle cells and in vivo in Sprague Dawley rats after tail vein injection. In the rat model, the PTX-NaHCO3-PLGA NPs treatment group showed suppressed intimal proliferation following balloon-induced carotid artery injury compared with that of the saline-treated control. Overall, these results demonstrate that our newly developed pH-responsive nanodrug delivery platform has the potential to effectively inhibit restenosis.